The Semantically Rich Learning Environments: A Systematic Literature Review - Hamidreza Rostami; Shaban Elahi; Ali Moeini; Alireza Hassanzadeh (International Journal of Digital Content Management, 2021)
Purpose: The research is intended to extract repetitive themes in the field of semantic-rich learning and to express the basic opportunities and challenges therein.Method: The method applied was to review the articles published in the WOS database, during the years 2000 to 2020 by using the paradigm funnel technique; moreover the Nvivo software was used for document analysis and theme extraction.Findings: In the study, it was found that establishing access to appropriate educational content, proper analysis and representation of knowledge, human capabilities enhancement, personalization of learning, and improving the quality of assessment, are the most important positive effects of using STs in learning; Also, in this study, nine themes and seven major challenges in the field of semantic-rich learning were identified.Conclusion: personalization and adaptation, and the development of various ontologies, are the most cited themes; and access to learning content and concerns about the design and development of learning systems are the most important challenges facing semantic-rich learning environments. We believe that in order to overcome the enumerated challenges, the combination of STs with other emerging cognitive and communication technologies, such as IoT, is necessary and could be the subject of future research in this field.